2019
DOI: 10.1177/1369433219884462
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and numerical analysis of the stress concentration factor for concrete-filled square hollow section Y-joints

Abstract: Previous studies have shown that the stress concentration factors for 90° square hollow section T- and X-joints can be significantly reduced by filling the chord with concrete and stiffening the chord with perfobond ribs. The current study examined stress concentration factors for non-90° (Y-type) joints. A total of 11 Y-joints were tested under axial tension, and the hot spot stresses were measured. The measured results were employed to evaluate the influence of design parameters on the stress concentrations.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 23 publications
(29 reference statements)
0
1
0
Order By: Relevance
“…Yang et al (2015) and Chen et al (2016) carried out investigations on SHS concrete-fillled double skin tube. Jiang et al (2019a), Jiang et al (2019b), Jiang et al (2019c) and Jiang et al (2020) carried out experimental investigations and numerical analysis on concrete-filled joints with perfobond ribs under different load cases. It was found that concrete filling the chords and the use of perfobond ribs stiffening reduced the SCFs in comparison to the empty SHS joints.…”
Section: Introductionmentioning
confidence: 99%
“…Yang et al (2015) and Chen et al (2016) carried out investigations on SHS concrete-fillled double skin tube. Jiang et al (2019a), Jiang et al (2019b), Jiang et al (2019c) and Jiang et al (2020) carried out experimental investigations and numerical analysis on concrete-filled joints with perfobond ribs under different load cases. It was found that concrete filling the chords and the use of perfobond ribs stiffening reduced the SCFs in comparison to the empty SHS joints.…”
Section: Introductionmentioning
confidence: 99%